Understanding the adoption of high-iron varieties in Maharashtra, India: What explains popularity? - Smale, Melinda; Diressie, Michael Tedla; Birol, Ekin (International Food Policy Research Institute, 2016)
Pearl millet is one of the most important food staples of poorer populations in the drylands of India. India’s first pearl millet hybrids were released during the Green Revolution. Low seed costs and the privatization of the national seed industry spurred diffusion of pearl millet hybrids once resistance to downy mildew had been achieved. Across Indian states, adoption rates for pearl millet hybrids are among the highest in the State of Maharasthra, where the government has encouraged a dynamic, competitive seed industry. To our knowledge, no recent large-scale adoption studies have been conducted in Maharashtra. With the aim of better understanding the potential market for high-iron, pearl millet hybrids, we explore factors associated with growing pearl millet, and those that influence whether farmers grow major (popular) hybrids, as compared with minor cultivars. We test the relationships among cultivar choice, seed, and information sources. The data confirm that pearl millet is more likely to be grown by poorer households in drier, drought-prone areas. Scheduled castes are more likely to grow popular hybrids, and less likely to grow minor cultivars, but are no less likely to acquire seed from commercial vendors (including agro-dealers and agri-service centers) than less privileged people. Farmers who grow major (minor) hybrids also ascribe less (more) importance to marketing traits then either consumption or production traits. Iron content is not an observable trait. Thus, de facto, popular pearl millet varieties are likely to reach less privileged farmers. To attach adoption potential, popular hybrids could be targeted for iron enrichment, and commercial marketing strategies should be pursued.